Input output models for estimating suspended sediment flow - Kumar, Devendra; Rastogi, R A (Journal of Agricultural Engineering, 2000)
Linear discrete input-output models were developed for estimating sediment discharge hydrographs from the Chaukhutia watershed comprising an area of 452.25 kmÂ² of the Ramganga reservoir catchment. The causative factors such as sediment mobilized, direct runoff and excess rainfall water was used as input to the models and sediment discharge as the output. The parameters of these models were estimated from rainfall hyetographs, direct runoff hydrographs and direct sediment flow graphs by Lagrangian's method. The generation and prediction performance of these models were assessed based on pattern recognition technique and using the criteria of accuracy. The computed sediment graphs were in closer agreement with measured sediment flow graphs. The average values of coefficient of efficiency and relative error in estimated peak for sediment mobilized-sediment discharge model were more than 96.0% and less than 7.6 %, respectively whereas for direct runoff-sediment discharge model the values were more than 79.0% and less than 18.8%, respectively. For rainfall excess-sediment discharge model these values were more than 57.0% and less than 29.0, respectively.